Troubleshooting Docker - Kohli, Vaibhav; Kohli, Vaibhav; Dua, Rajdeep; Wooten, John (Packt Publishing, 2017)
Strategically design, troubleshoot, and automate Docker containers from development to deploymentAbout This BookUtilize current and emergent technologies for effective Docker orchestration and managementA step-by-step guide to diagnosing and fixing problems with Docker containers.Who This Book Is ForThis book is intended for seasoned solutions architects, developers, and programmers, system engineers, and administrators to help you troubleshoot common areas of Docker containerization. If you are looking to build production-ready Docker containers for automated deployment, you will be able to master and troubleshoot both the basic functions and the advanced features of Docker. Advanced familiarity with the Linux command line syntax, unit testing, the Docker Registry, Github, and leading container hosting platforms and Cloud Service Providers (CSP) are the prerequisites.What You Will LearnInstall Docker ecosystem tools and services, Microservices and N-tier applicationsCreate re-usable, portable containers with help of automation toolsNetwork and inter-link containersAttach volumes securely to containersConsume and troubleshoot Docker APIsTroubleshooting issue of Docker deployment in Public cloudEase the process of container management with KubernetesIn DetailThis book will traverse some common best practices to for complex application scenarios where troubleshooting can be successfully employed to provide the repeatable processes and advantages that containers can deliver.This book will be a practical guide showing how to fix real-life issues related to installation, memory, Dockerfile syntax, connection, authorization, networking and so on in Docker. This book will also teach how to solve errors that occur during advanced setup and administration and deployment in a step-by-step fashion. By sequentially working through the real-world production scenarios in each chapter throughout the book, you will gain insight into and mastery of common areas not only for effective troubleshooting, but ways and means to avoid troubleshooting in the first place. This book will also cover tips and tricks that make the workflow easier.Style and approachAn easy-to-follow guide full of interactive examples of real-world development and deployment scenarios.Ample screenshots, workflows, complementary tools, and related terminal commands are provided to address a wide range of practical and situational applications.